INCREASE THE RESOURCE OF CURRENT COLLECTOR ELEMENTS OF THE ELECTRIFIED HIGH-SPEED TRANSPORT IN OPERATING CONDITIONS - Bolshakov, Y. L.; Antonov, A. V. (Science and Transport Progress, 2015)
Purpose. The paper is aimed to determinate the main ways of increasing resource efficiency and exploitation of coal current collector surface inserts of speed electric rolling stock. Methodology. The research is based on the technique relies on the use of theory regulations of technical systems reliability, electromechanical processes, theory of statistics. Findings. The existing approaches to the production of current collector surface inserts in Europe and Ukraine were considered, a number of information sources was analyzed. The most effective ways of increasing current carrying capacity and wear resistance of current collector elements were determined. It has been established that the existing system for determining the quality of manufacturing of current collector elements have a number of drawbacks that make it difficult to control the input and makes diagnosing current collecting elements in operation impossible. On the basis of the facts, for the needs of the locomotive depot, we propose a new booth allowing avoiding the existing difficulties with diagnosing of current collector elements. During the study were established pervasive transgressions of technological standards of service pantographs. Originality. Based on the results of operational research carried out on the basis of the locomotive depot, obtained depending, based on which, it is proposed to introduce an operative diagnosing system of the current collector elements state during operation. In the course of a comparative analysis of existing and perspective development directions of current collector elements with high load current carrying capacity and durability, were definited constructive conditions for the optimal ratio is inserts. It was established that a significant proportion of failures occur due to imperfect maintenance system for which, on the basis of operational data, recommendations were developed. Practical value. Obtained results of the information sources analysis determine the need to implement coal inserts copper component in material, which will increase the load current carrying capacity of the current collectors. The numerous shortcomings of existing diagnostic systems carbon of current collector inserts skids pantographs were established, the solution of them should be the basis for the development of new means and diagnostic systems of current collector elements. It can improve service life of inserts and arrange culling of substandard of current collector inserts. The imperfect system maintenance of pantographs was established. The requirements increasing to this system will significantly reduce the amount of breakages caused by an increased transitive resistance in the «insert – pantograph».